Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jdent.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties and compressive strength of new one-step preparation silver nanoparticles in glass ionomer cements (NanoAg-GIC)

Abstract: Silver nanoparticles one-step preparation in polyacrylate solution allowed the production of highly bioactive water-based cements within suitable parameters for clinical use and with large potential of dental and biomedical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 54 publications
2
51
0
1
Order By: Relevance
“…However, concentrations of fluoride released from GICs are too low to effectively inhibit the growth of oral bacteria [7][8][9] . Therefore, several attempts have been made to provide GICs with antibacterial effects by adding antimicrobial components such as chlorhexidine [10][11][12] , quaternary ammonium compounds 13) , silver nanoparticles 14) , epigallocatechin-3-gallateor 15) , and propolis extract 16) .…”
Section: Introductionmentioning
confidence: 99%
“…However, concentrations of fluoride released from GICs are too low to effectively inhibit the growth of oral bacteria [7][8][9] . Therefore, several attempts have been made to provide GICs with antibacterial effects by adding antimicrobial components such as chlorhexidine [10][11][12] , quaternary ammonium compounds 13) , silver nanoparticles 14) , epigallocatechin-3-gallateor 15) , and propolis extract 16) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, nanoglasses, chlorhexidine, chitosan, and metallic nanoparticles have been applied as antibacterial and antifungal additives [10]. Corresponding in vitro or in vivo trials showed differing effectiveness of these modifications, but none of these antimicrobial alterations has prevailed over the others or is actually widely used in dentistry [11][12][13][14][15]. The luting materials tested in the present study are zinc oxide phosphate cements (ZOP), representing the most common conventional luting material in dentistry [1].…”
Section: Introductionmentioning
confidence: 96%
“…Studies have shown, AgNPs synergize the e cacy of antibiotics like amoxicillin, clindamycin, vancomycin and penicillin G against various microbes [13,14]. Because of its antimicrobial activity and synergizing effects, researchers have studied the use of AgNPs in several areas of dentistry which include dental biomaterials [15][16][17], dental implants [18], orthodontic adhesives [19] etc. In vitro studies have shown, addition of AgNPs in to dental restorative materials inhibit growth of common oral microbes like Streptococcusmutans, Streptococcus sanguinis,and Lactobacillus through bactericidal and bacteriostatic effects of AgNPs on oral microbes [16,20] without altering its mechanical properties [21].…”
Section: Introductionmentioning
confidence: 99%